Determination of anti-cancer properties of urtica dioica ethanol extract on hematopoietic cell lines - MEGA TİBER, PINAR; ŞEN, ALİ; ORUN, OYA (My University, 2022)
Aim: Urtica dioica is a natural phytotherapeutic agent with various effects such as antioxidant, anti-inflammatory, anti-fungal, hypotensive as well as anti-carcinogenic. In recent years, phytotherapeutic approaches to reduce side effects of available chemotherapeutic agents or to find new agents with higher toxicity in cancer cells relative to healthy ones, are area of intense research. Therefore, in this study, we investigated anti-carcinogenic effects of U. dioica ethanol extract on K562 human chronic myeloid erythrocyte cell lines and on lymphocytes isolated from healthy donors (PBMC).Material and Methods: U. dioica extract was isolated by using soxhlet extraction methodology. Anti-carcinogenic effects of the agent were analyzed with MTT assay (Cell Proliferation Kit I, Roche), Annexin V/PI (Molecular Probes A10788), mitochondrial membrane potential assay (JC-1, Abnova KA1324) and cell cycle analyses (PI staining in flow cytometer (FACS Calibur). PBMCs were prepared from healthy volunteers through Ficoll Hypaque density gradients.Results: Data indicated that treatment with U. dioica didn’t show up a dose-dependent cytotoxic effect on K562 cell line, but there was a 20% suppression at 25 μg/ml compared to PBMC (p<0.001). U. dioica extract yielded to an increase in apoptosis 13% and 41% for 25 μg/ml and 100 μg/ml, respectively, in comparison to untreated control cells (p=0.033). It has also induced cell cycle arrest at G0/G1 phase, in a dose-dependent manner. Accumulation at G0/G1 phase increased 9.6, 10 and 14% in 50, 75 and 100 μg/ml concentrations, respectively, compared to the control group (p<0.0001).Conclusion: Our findings explicitly show that the total ethanol extract of U. dioica is highly effective in K562 cells on the induction of apoptosis and cell cycle arrest at reasonably low concentrations and these effects significantly pronounced compared to healthy controls.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)